Deep Brain Stimulation Complications in Patients With Parkinson’s Disease and Surgical Modifications: A Single-Center Retrospective Analysis - Xu, Shuo; Wang, Wenfei; Chen, Si; Wu, Qianqian; Li, Chao; Ma, Xiangyu; Chen, Teng; Li, Weiguo; Xu, Shujun (Frontiers in Human Neuroscience, 2021)
Background: As a complication-prone operation, deep brain stimulation (DBS) has become the first-line surgical approach for patients with advanced Parkinson’s disease. This study aimed to evaluate the incidence and risk factors of DBS-associated complications. Methods: We have reviewed a consecutive series of patients with Parkinson’s disease undergoing DBS procedures to describe the type, severity, management, and outcome of postoperative complications from January 2011 to December 2018. Both univariate and multivariate analyses were performed to identify statistically significant risk factors. We also described our surgical strategies to minimize the adverse events. Results: A total of 225 patients underwent 229 DBS implantation procedures (440 electrodes), of whom 20 patients experienced 23 DBS-associated complications, including ten operation-related complications and 13 hardware-related ones. Univariate analysis elucidated that comorbid medical conditions (P =0.024), hypertension (P =0.003), early-stage operation (P <0.001), and unilateral electrode implantation (P =0.029) as risk factors for overall complications, or more specifically, operation-related complications demonstrated in the stratified analysis. In contrast, no risk factor for hardware-related complications was identified. Statistical significances of hypertension (OR=3.33, 95% CI: 1.14-9.71, P =0.027) and early-stage (OR=11.04, 95% CI: 2.42-50.45, P =0.002) were further validated via multivariate analysis. As the annual number of DBS procedures increased, the incidence of complications gradually decreased (R=-0.699, P <0.01). Additionally, there was a strong correlation between surgical complications and unplanned readmission (R=0.730, P <0.01). Conclusion: The importance of cumulative experience and relevant technique modifications should be addressed to prevent DBS-associated complications and unplanned readmission.